Wiley Encyclopedia of Operations Research and Management Science 2011
DOI: 10.1002/9780470400531.eorms0634
|View full text |Cite
|
Sign up to set email alerts
|

Overweighting of Small Probabilities

Abstract: The psychological impact of a low probability or rare event is typically large relative to that of the event's actuarial likelihood. This overweighting follows a two‐stage process. First, rare events tend to be overestimated because of the availability heuristic, anchoring on the “ignorance prior,” and coarse chance categories. Second, when making decisions, low probability events are overweighted because of the “possibility effect”—decision makers are more sensitive to probability chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…In each 30 students group, students were promised a 30€ prize by drawing lots. This incentive compatibility method was preferred because of the well-known bias leading people to overweight small probabilities (Chen and Jia, 2005;Burns, Chiu and Wu, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…In each 30 students group, students were promised a 30€ prize by drawing lots. This incentive compatibility method was preferred because of the well-known bias leading people to overweight small probabilities (Chen and Jia, 2005;Burns, Chiu and Wu, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…In our research context, substitution is a conjunctive event since it is possible only when there is a shortage of the economy cars and there is a surplus of mid-sized cars, as evident from (6). Additionally, there is also prior evidence that decision makers attach larger than optimal weights to rare events in terms of their impact on decisions (e.g., Burns et al, 2010;Bilgin, 2012). In our context, this finding implies that decision makers are likely to over-estimate the quantity of units substituted based on overinflated weighting or easier recollection of rare instances of particularly severe shortages.…”
Section: Estimation Of Frequency Quantity and Value Of Substitutionmentioning
confidence: 64%
“…Briefly, prior research has suggested that decision-makers tend to overestimate the probability of infrequent events. This has been attributed to availability bias (instances of product shortage gain attention and may come more readily to mind), and a tendency to start with a large estimated value followed by insufficient adjustment (e.g., Lichtenstein et al, 1978;Armantier, 2006;Burns et al, 2010). Chen and Jia (2005) show that the overestimation is proportional to the payoff or potential loss associated with an infrequent event.…”
Section: Estimation Of Frequency Quantity and Value Of Substitutionmentioning
confidence: 99%
“…The term deposit would seem to create less aversion to a "bottles" tax, even though the underlying logic of deposit programs is to tax the act of throwing bottles into the general waste stream. 8 An alternative explanation is the overweighting of low probabilities that is documented by numerous studies (Burns et al 2010;Tversky & Fox 1995). tion: enjoyment-based and obligation-based (Osterloh, Frey, & Frost 2001: 233;Ryan & Deci 2000: 70).…”
Section: Crowding Out and The Optimal Size Of Legal Incentivesmentioning
confidence: 99%